AJANG: INNOVATIVE PRODUCTS IN THE APPLICATION OF SCIENCE CONCEPTS BASED ON LOCAL POTENTIAL - Zunika Agung Rahayu; Ornella Alika; Achmad Buchori (Universitas PGRI Semarang, 2024)
Learning innovation plays an important role in improving students' understanding of science concepts. This research introduces an innovative product, Abon Jantung Pisang (AJANG), which is integrated in the learning of Natural Science (IPAS) by 5th grade students of State Elementary School 1 Jugo. AJANG serves as an alternative utilization of local potential as well as interactive learning media. The method used is a project-based approach, where students are directly involved in the process of making shredded banana hearts. Through this activity, students learn aspects of science, including the benefits of plants, food processing and entrepreneurial values. The results of the application of AJANG in the curriculum showed an increase in the understanding of science concepts and students' interest in learning by utilizing local potential that exists arounds students. Thus, this research is expected to contribute to the development of local potential-based learning innovations and increase students' awareness of the importance of sustainable utilization of natural resources.